(untitled) (Palíndromo, 2021)
In the context of the global health crisis, our research started four years ago on the question of how to reconcile the teaching of the plastic arts and their practice within the training of the future teacher of schools when there is less and less hours of face-to-face lessons is all the more a topical subject. Indeed, at the present time, university courses are conducted remotely. Our study thus raises the question of the quality and content of the distance course in order to bring about plastic practices among students, future teachers. The hourly decline of this teaching over the past few decades questions the legitimacy, the stakes and the place of the student’s plastic practice. Likewise, the changes and challenges of teaching methods, particularly the emergence of hybrid training through the use of digital technology, question posture changes in the trainer.